Association between multimorbidity and hospitalization in older adults: systematic review and meta-analysis. (23rd July 2022) - Rodrigues, Luciana Pereira; de Oliveira Rezende, Andréa Toledo; Delpino, Felipe Mendes; Mendonça, Carolina Rodrigues; Noll, Matias; Nunes, Bruno Pereira; de Oliviera, Cesar; Silveira, Erika Aparecida
Abstract: Background: Multimorbidity is defined as the presence of multiple chronic conditions in the same individual. Multimorbidity is more prevalent in older adults and can lead to several adverse health outcomes. Methods: We systematically reviewed evidence from observational studies to verify the association between multimorbidity and hospitalization in older adults. Furthermore, we also aimed to identify whether it changes according to gender, advanced age, institutionalization, and wealth of the country of residence. We searched the PubMed, Embase and Scopus databases from December 2020 to April 2021. The analysed outcomes were as follows: hospitalization, length of stay and hospital readmission. Results: Of the 6, 948 studies identified in the databases, 33 were included in this review. From the meta-analysis results, it was found that multimorbidity, regardless of the country's wealth, was linked to hospitalization in older adults (OR = 2.52, CI 95% = 1.87–3.38). Both definitions of multimorbidity, ≥2 (OR = 2.35, 95% CI = 1.34–4.12) and ≥3 morbidities (OR = 2.52, 95% CI = 1.87–3.38), were associated with hospitalization. Regardless of gender, multimorbidity was associated with hospitalization (OR = 1.98, 95% CI = 1.67–2.34) and with readmission (OR = 1.07, 95% CI = 1.04–1.09). However, it was not possible to verify the association between multimorbidity and length of stay. Conclusions: Multimorbidity was linked to a higher hospitalization risk, and this risk was not affected by the country's wealth and patient's gender. Multimorbidity was also linked to a higher hospital readmission rate in older adults. PROSPERO Registration (Registration number: CRD42021229328).